Chapter Per un profilo di Francesco Soderini, pittore «assai ragionevole nella storia e nei paesi, in grande e più in piccolo» - Leonelli, Lisa (Studi e saggi, 2020)
Francesco Soderini (1671-1736), father of Mauro Soderini (1703-1751), was a Florentine painter who worked for the last members of the Medici dynasty, expecially for the Electress of the Palatinate Anna Maria Luisa, the only daughter of the granduke Cosimo III de' Medici. Among the artist's works, only the paintings for Villa La Quiete, the place where Anna Maria Luisa stayed during her last years, are well studied. This paper proposes new attributions to Soderini by recognising his style in some canvases presented on the art market and attributed to anonymous artists. These paintings contribute to a more accurate acknowledgement of the artist and of his style, which was very appreciated by his contemporaries.